The Philosophical meanings contained Serat Sari Swara entitled Wasita Rini Song by Ki Hadjar Dewantara - Akbar Al Masjid; Sumarlam Sumarlam; Retno Winarni; Budhi Setiawan; Trisharsiwi Trisharsiwi; Suhailee Sohnui; Arya Dani Setyawan; Endah Marwanti (Universitas Sarjanawiyata Tamansiswa, 2023)
Serat Sari Swara is an old literary work (1930) written directly by KHD using Javanese script and in Javanese in the form of tembang (poetry genre). This study of old literary works is important because it is an intellectual heritage of the work of the Father of the Indonesian National Education (KHD), which contains many moral and philosophical teachings that are useful as lessons and knowledge for the current generation. The data analysis method used is the content analysis method through the perspective of literary interpretation. The primary data source of this research comes from the Serat Sari Swara script, especially the Asmaradana Wasitarini songs. The results of the research on the philosophical meaning of the Asmaradana Wasita Rini song are about advice and teaching to women in fighting for their rights to obtain gender equality and women's independence, as well as the dedication of women (wives) to men (husbands) so that they can live in harmony and happiness. In detail, the contents of Wasita Rini's philosophical meaning are as follows: 1) teachings to women to always maintain the norms of decency and decency; 2) Protect themselves and their honour; 3) Women need to be respected and respected and do not like being treated arbitrarily; 4) can control themselves; 5) A woman must be conscientious and good at sorting out good and bad things; 6) Women must have the intelligence of creativity, taste, and intention (morals).